Essential Oil of Solanum spirale Fruits and Its Biological Activities - Sukanya Keawsa-ard (Science Faculty of Chiang Mai University, 2019)
The essential oil of Solanum spirale Roxb. unripe fruits was analyzed for the first time using GC-MS. Twenty-nine constituents were identified, constituting 82.11% of the total chromatographical oil components. The major components were n-hexadecanoic acid (56.01%), linolelic acid (9.71%), octadecanoic acid (4.41%), methyl plamitate (1.69%), tetradecanoic acid (1.55%), (E)-phytol (1.18%), n-hexanal (0.91%), methyl salicylate (0.83%), 4-hydroxy-4-methylpentan-2-one (0.81%), pentadecanoic acid (0.71%) and b-selinene (0.56%). The oil exhibited anticancer activities against MCF-7 (breast cancer) and NCI-H187 (small cell lung cancer) with the IC50 values of 23.17 and 49.07 µg/mL, respectively. It exhibited antituberculosis activity against Mycobacterium tuberculosis H37Ra with the MIC value of 50.0 µg/mL and it also showed moderately antibacterial activity against Escherichia coli and Staphylococcus aureus with the MIC values of 118 mg/mL.